For you and only you [large type] - Kepnes, Caroline, 1976- (Kepnes, Caroline, 1976- You novel., 2023)
"Joe Goldberg is ready for a change. Instead of selling books, he's writing them. And he's off to a good start. Glenn Shoddy, an acclaimed literary author, recognizes Joe's genius and invites him to join a tight-knit writing fellowship at Harvard. Finally, Joe will be in a place where talent matters more than pedigree . . . where intellect is the great equalizer and anything is possible. Even happy endings. Or so he thinks, until he meets his already-published, already-distinguished peers, who all seem to be cut from the same elitist cloth. Thankfully, Wonder Parish enters the picture. They have so much in common. No college degrees, no pretensions, no stories from prep school or grad school. Just a love for literature. If only Wonder could commit herself to the writing life, they could be those rare literary soulmates who never fall prey to their demons. Wonder has a tendency to love, to covet, but Joe is a believer in the rule of fiction: If you want to write a book, you have to kill your darlings. With her trademark satirical, biting wit, Caroline Kepnes explores why vulnerable people bring out the worst in others as Joe sets out to make this small, exclusive world a fairer place. And if a little crimson runs in the streets of Cambridge . . . who can blame him? Love doesn't conquer all. Often, it needs a little push."--Provided by publisher.